(untitled) (Orfeu, 2017)
This article presents an analysis of the Kyrie in Alberto Nepomuceno’s Mass in D minor (1915), one of the goals being to identify stylistic features and musical intertextual relations. In relation to form, texture and timbre, Nepomuceno’s Kyrie presents great similarity to the Kyrie of Lorenzo Perosi, Missa Te Deum Laudamus (1899). As concerns harmony, the piece denotes a kind of modal character, possibly due to the organ techniques which accompany the gregorian chant. Regarding melody and prosody, there is a certain proximity to gregorian melodic contours, considered at the time as a paradigm of catholic church music.